Fabrication of starch‐g‐poly(l‐lactic acid) biocomposite films: Effects of the shear‐mixing and reactive‐extrusion conditions. Issue 13 (28th November 2016) - Salimi, Kouroush; Şen, Selin Cansu; Ersan, Hülya Yavuz; Pişkin, Erhan
ABSTRACT: In this study, we developed a new approach for the fabrication of a green poly(l ‐lactic acid)‐grafted starch (St‐ g ‐PLA) copolymer and nanocomposite (St‐ g ‐PLA/organoclay)‐based films via shear‐mixing and reactive‐extrusion systems. The chemical and physical structures, thermal behavior, and morphology of the synthesized blends and some other parameters were examined by Fourier transform infrared spectroscopy and 1 3 C cross‐polarization/magic angle spinning NMR spectroscopy, X‐ray diffraction, thermogravimetric analysis–derivative thermogravimetry, and scanning electron microscopy, respectively. Significant increases in the mechanical and permeability properties were evident in the high value of grafted poly(lactic acid) molar percentages and high exfoliation of organoclay. The biodegradability of films were investigated under aerobic composting conditions through the measurement of the temperature, moisture, pH, consumed O2 value, and carbon dioxide produced. This new strategy mainly improved the good adhesion between both phases, and it was an interesting method for the production of environmentally friendly biocomposites that could easily be scaled up for commercial production with the potential for replacing petroleum‐based plastics. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44490. Abstract :